Microbial extracellular electron transfer and its relevance to iron corrosion. Issue 2 (10th February 2016) - Kato, Souichiro
Summary: Extracellular electron transfer (EET) is a microbial metabolism that enables efficient electron transfer between microbial cells and extracellular solid materials. Microorganisms harbouring EET abilities have received considerable attention for their various biotechnological applications, including bioleaching and bioelectrochemical systems. On the other hand, recent research revealed that microbial EET potentially induces corrosion of iron structures. It has been well known that corrosion of iron occurring under anoxic conditions is mostly caused by microbial activities, which is termed as microbiologically influenced corrosion (MIC). Among diverse MIC mechanisms, microbial EET activity that enhances corrosion via direct uptake of electrons from metallic iron, specifically termed as electrical MIC (EMIC), has been regarded as one of the major causative factors. The EMIC‐inducing microorganisms initially identified were certain sulfate‐reducing bacteria and methanogenic archaea isolated from marine environments. Subsequently, abilities to induce EMIC were also demonstrated in diverse anaerobic microorganisms in freshwater environments and oil fields, including acetogenic bacteria and nitrate‐reducing bacteria. Abilities of EET and EMIC are now regarded as microbial traits more widespread among diverse microbial clades than was thought previously. In this review, basic understandings of microbial EET and recent progresses in the EMIC research are introduced. Abstract : Extracellular electron transfer (EET) is a microbial metabolism that enables efficient electron transfer between microbial cells and extracellular solid materials. Recent research revealed that microbial EET potentially induces corrosion of iron structures. In this review, basic understandings of microbial EET and its relevance to iron corrosion are introduced.